First Experiences with MANTA Vascular Closure Device in Minimally Invasive Valve Surgery - Ahmad, Ali El-Sayed; Salamate, Saad; Amer, Mohamed; Sirat, Sami; Monsefi, Nadejda; Bakhtiary, Farhad (The Thoracic and Cardiovascular Surgeon, 2020)
Background To more minimize the minimally invasive valve surgeries, percutaneous vascular access and closure has been used for the establishment of extracorporeal circulation. This study investigates early clinical outcomes of patients who received MANTA for femoral artery closure as first experiences in minimally invasive valve surgery.Methods Between January 2019 and July 2019, 103 consecutive patients (mean age: 58 ± 11 years) underwent video-assisted minimally invasive valve surgery through right anterior minithoracotomy at two cardiac surgery referral centers in Germany. Percutaneous cannulation for cardiopulmonary bypass and femoral artery closure with MANTA were performed in all patients: 18-F and 14-F MANTA were used in 88 (85.4%) and 15 (14.6%) patient, respectively. Mitral, aortic, tricuspid, and double valve surgeries were performed in 51 (49.5%), 39 (37.9%), 7 (6.8%), and 6 (5.8%), patients, respectively. Clinical data were prospectively entered into our institutional database.Results Cardiopulmonary bypass time and cross-clamping time were 69 ± 23 and 38 ± 14 minutes, respectively. Except for two patients with late pseudoaneurysm on 15th and 23th postoperative day, neither major nor minor vascular complications nor vascular closure device failure according to the Valve Academic Research Consortium-2 definition criteria was observed. Additionally, no wound healing disorders or conversion to surgical closure was observed.Conclusions MANTA as percutaneous femoral artery closure after decannulation of cardiopulmonary bypass is a safe, feasible, and effective approach and yields excellent early outcomes. Larger size studies are needed to evaluate more the efficacy and safety of MANTA.
Keywords: heart valve surgery; minimally invasive valve surgery; outcomes